2013
DOI: 10.1007/s00442-013-2663-2
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for parasites in the maintenance of color polymorphism in urban birds

Abstract: Urbanization is a major challenge for biodiversity conservation, yet the evolutionary processes taking place in urbanized areas remain poorly known. Human activities in cities set new selective forces in motion which need to be investigated to predict the evolutionary responses of animal species living in urban areas. In this study, we investigated the role of urbanization and parasites in the maintenance of melanin-based color polymorphism in the feral pigeon Columba livia. Using a correlative approach, we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 58 publications
4
39
0
2
Order By: Relevance
“…In the support of the first possibility, Galeotti & Sacchi [9] found that rufous-morph tawny owls (Strix aluco) hosted higher total blood parasite burdens than grey morphs owing to both greater exposure to vectors and greater susceptibility to parasites. In feral pigeons (Columba livia), alternative morphs were distributed non-randomly across an urban gradient and had different parasite risks [15]. However, the different Eleonora's falcon morphs inhabit small islands sympatrically during the breeding season and local transmission of blood parasites at breeding grounds is absent, owing to the lack of suitable vectors [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the support of the first possibility, Galeotti & Sacchi [9] found that rufous-morph tawny owls (Strix aluco) hosted higher total blood parasite burdens than grey morphs owing to both greater exposure to vectors and greater susceptibility to parasites. In feral pigeons (Columba livia), alternative morphs were distributed non-randomly across an urban gradient and had different parasite risks [15]. However, the different Eleonora's falcon morphs inhabit small islands sympatrically during the breeding season and local transmission of blood parasites at breeding grounds is absent, owing to the lack of suitable vectors [16].…”
Section: Discussionmentioning
confidence: 99%
“…Both direct (metal binding) and indirect (resistance to parasites, oxidative stress and physiological stress) associations between biological traits and plumage melanism may favour darker birds in environments polluted with trace metals. Accordingly, previous studies observed a higher frequency of melanistic feral pigeons in European cities (Obukhova, ; Jacquin et al ., ), where environmental concentrations of metals are the highest (Azimi et al ., ; Scheifler et al ., ; Roux & Marra, ; Kekkonen et al ., ). However, there is no experimental evidence for fitness advantages of being more melanistic in habitats polluted with trace metals.…”
Section: Introductionmentioning
confidence: 99%
“…The potential effects of metals on animal coloration have been the focus of several studies in the last 15 years, with a special interest on the relationships between exposure to these metals and the deposition of the two most common pigments of the vertebrate tegument: the carotenoid and melanin pigments (Chatelain et al, 2014;Dauwe and Eens, 2008;Geens et al, 2009;McGraw, 2003, 2008, Niecke et al, 2003Roulin et al, 2006). So far, melanin pigmentation seems to be positively associated with metal exposure in wild birds since (1) more pigmented individual feral pigeons (Columba livia) are found in urban compared to rural environments (Jacquin et al, 2013;Obukhova, 2007), (2) darker feral pigeons had higher concentrations of zinc in their feathers compared to paler ones after one year in standardized conditions (Chatelain et al, 2014), (3) copper deficiency influences plumage color in poultry species (Leeson, 2009;Leeson and Walsh, 2004) and (4) melanin pigmentation in great tits (Parus major) increases along a gradient of metal pollution caused by a lead smelter in Belgium (Dauwe and Eens, 2008). Two main hypotheses have been proposed to explain this association.…”
Section: Introductionmentioning
confidence: 99%